Liverpool shipping records : imports and exports, 1820-1900 - Part 1. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2013)
The Livepool Customs Bills of Entry were printed broadsheets designed to provide factual information - primarily statistics - for merchants and other interested parties to keep abreast of the flow of commerce into and out of the port. Liverpool is an appropriate port for examining the details of ships and their cargoes in depth, for it rose significantly to become an important maritime centre during the eighteenth century. It was a rise that followed the pouring of millions of pounds by the wealthy city corporation into constructing wet docks that became the envy of other British ports. Liverpool shippers became significant traders in the Caribbean sugar and Chesapeake tobacco trades but, above all, in the African slave trade to the Americas, so that by 1800 Liverpool was the largest slave trading port in the world. In the nineteenth century the port of Liverpool grew even larger with industrialisation, the financing of additional docks, internal links with the canal and railway network, the growth of the cotton trade with the United States, the rise of the emigrant trade, and the development of successful steamship companies such as Blue Funnel and the Guinea, Bibby and Castle lines. By the 1840's, Liverpool handled more export tonnage than London. Many of these commercial trends can be analysed via the Bills of Entry. Collectively drawn from the Liverpool Record Office and Liverpool Maritime Museum, these Bills of Entry are complete for the period 1820-1900 with the exception of the years 1821-24, 1833, 1836 and 1838-40 where lacunae exist. This description was drawn from the introduction and online guide to the microfilm edition by Professor Kenneth Morgan of Brunel University.
Date range: 1820-1860.
Keywords: Shipping -- England -- Liverpool